2009
DOI: 10.1891/1541-6577.23.2.148
|View full text |Cite
|
Sign up to set email alerts
|

The Rhythm of Health in Older Women With Chronic Illness

Abstract: Trends in population growth indicate that nurses increasingly will be caring for older adults, especially older women, who are at risk for less than optimal health due to chronic illnesses. The purpose of this qualitative study was to obtain a better understanding of the meaning of health from the perspective of older women. Focus group interviews with 51 women, aged 55 to 93, were held. Data were analyzed using directed qualitative content analysis. A Rogerian perspective of human health provided the broad co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Health is a key concept of nursing (Crawford‐Shearer et al ., 2009). The definition of health has developed alongside the growth of knowledge and theories over time (Jiuan, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Health is a key concept of nursing (Crawford‐Shearer et al ., 2009). The definition of health has developed alongside the growth of knowledge and theories over time (Jiuan, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Three of the five concepts in the Evolutionary Empowerment-Strength model were supported, which demonstrated initial usefulness of the model for varied populations. Shearer, Fleury, and Reed (2009) used focus group interviews with 51 women, aged 55 to 93 years, to obtain a deeper understanding of the meaning of health from the perspective of elderly women. A Rogerian perspective of human health provided a broad conceptual lens for the study.…”
mentioning
confidence: 99%
“…Three themes explicating the meanings of health emerged from the data: realizing the potential for purpose, listening to energy flow, and purposefully participating in health-related changes. The three themes represented the manner in which the women contended with the paradoxes posed by their chronic illnesses (Shearer et al, 2009).…”
mentioning
confidence: 99%
“…Across research sites, participants have consistently emphasized the idea of health as the ability to function, to perform daily activities, and to be independent (e.g., Bishop & Yardley, 2010;Crawford Shearer, Fleury, & Reed, 2009;Fagerlind, Ring, Briilde, Feltelius, & Lindblad, 2010;Kenney, 1992;Mansour, 1994). Although is has been suggested in many studies that the absence of illness represents one dimension of health, other studies have shown that people consider that one can still be healthy despite an illness as long as one can still function (Laffrey & Crabtree, 1988;Kushner, 2007).…”
Section: Multidimensional Health Modelsmentioning
confidence: 99%
“…Other health practices include keeping track of one's current state of health, using health-care services, maintaining good relationships, engaging in pleasant activities, managing stress, and engaging in spiritual practices (Crawford Shearer et al, 2009;Goins et al, 2011;Kushner, 2007).…”
Section: Multidimensional Health Modelsmentioning
confidence: 99%